The Effect of Profitability, Leverage on Profit Management with Company Size as Moderation - Nurhidayah, Fitriyah; Farhatinnisa, Kamillah (International Economic Conference of Business and Accounting, 2024)
Earnings management is the practice of manipulating financial reports to achieve certain goals. Earnings management practices can be influenced by various factors. Therefore, this research aims to determine and prove the influence of the relationship between profitability, leverage on earnings management and company size as a moderating variable. The population in this study was 23 State-Owned Enterprises (BUMN) for the time period 2018 to 2022. The sample in this study consisted of 115 data that met the purposive sampling criteria. The research uses a quantitative approach using e-views 12 software to carry out data processing. The partial research results show that profitability has an effect on earnings management, while leverage has no effect on earnings management. Simultaneously profitability and leverage influence earnings management. In moderation, company size cannot moderate profitability on earnings management and company size can moderate leverage on earnings management. Keywords: Profitability; Leverage; Firm Size; Earnings Management